Qishen Granule (QSG) Inhibits Monocytes Released From the Spleen and Protect Myocardial Function via the TLR4-MyD88-NF-κB p65 Pathway in Heart Failure Mice - Li, Yanqin; Li, Xuan; Chen, Xu; Sun, Xiaoqian; Liu, Xiangning; Wang, Gang; Liu, Yizhou; Cui, Lingwen; Liu, Tianhua; Wang, Wei; Wang, Yong; Li, Chun (Frontiers in Pharmacology, 2022)
Preliminary clinical and basic research have proved that Qishen granule (QSG) is an effective prescription for treating heart failure (HF) in China, with a characteristic of regulating the ratio of M1/M2 macrophage in the myocardium. However, the regulative mechanism of monocytes targeting the cardio-splenic axis has not been fully elucidated. This study aimed to investigate the effects and mechanism of QSG inhibiting the release of splenic monocytes and the recruitment of myocardial tissue both in vivo and in vitro. Experiments in mice with acute myocardial infarction (AMI)-induced HF demonstrated that QSG could exert anti-inflammatory effects by inhibiting splenic monocytes release and phenotypic changes. Moreover, in vitro experiments indicated QSG could inhibit LPS-stimulated macrophage-conditioned medium (CM)-induced H9C2 cardiomyocyte injury by upregulating the key proteins in the TLR4-MyD88-NF-κB p65 pathway. In addition, knockdown or overexpression of TLR4 in H9C2 cells further confirmed that QSG could attenuate inflammatory injury in cardiomyocytes via the TLR4-MyD88-NF-κB p65 pathway. Overall, these data suggested that QSG could improve cardiac function and reduce the inflammatory response in AMI-induced HF by inhibiting splenic monocytes release and protecting myocardial function via the TLR4-MyD88-NF-κB pathway in heart failure mice